1998
DOI: 10.1530/jrf.0.1140341
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of vitamin E on ischaemia-reperfusion injury in ovarian grafts

Abstract: Ovarian cortical tissue cryopreservation with subsequent autografting is a potential strategy for the preservation of fertility in patients undergoing systemic chemotherapy and pelvic radiotherapy. Non-vascular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
2
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(111 citation statements)
references
References 21 publications
6
101
2
1
Order By: Relevance
“…In accordance with Nugent et al 2 who noted a temporary interruption of ovarian function after the transplant, the information in this study showed that this interruption lasted an average of 16 days in the transplanted groups, 12 days in the fresh grafts and 19 days in the cryopreserved grafts. However, this function re-initiates after the recruitment of the surviving primordial follicles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with Nugent et al 2 who noted a temporary interruption of ovarian function after the transplant, the information in this study showed that this interruption lasted an average of 16 days in the transplanted groups, 12 days in the fresh grafts and 19 days in the cryopreserved grafts. However, this function re-initiates after the recruitment of the surviving primordial follicles.…”
Section: Discussionsupporting
confidence: 92%
“…The longer the time course of angiogenesis, the shorter is graft survival. Thus, measures to accelerate revascularization are greatly expected by specialists 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al, [31] showed that the ovarian tissue could tolerate ischaemia for at least 2 h at 0°C or at room temperature, and that a water soluble antioxidant (ascorbic acid) reduces apoptosis in ovarian cortex by up to 24 h in the case of incubation in vitro. It has been reported that treatment with vitamin E, a lipid soluble antioxidant, improved the survival of follicles in ovarian grafts by reducing ischemic injury [32]. Prolonged exogenous stimulation promoted primordial follicle maturation but also caused a loss of primordial follicles in xenotransplanted frozen-thawed ovaries [28,33].…”
Section: Discussionmentioning
confidence: 99%
“…Nugent et al (22) tried to reduce damage by reactive oxygen species generated during ischemia and reperfusion by antioxidant vitamin E and achieved a significant improvement in follicle survival, from 45% to 72%. Schnorr et al found that VEGF administered subcutaneously at the site of ovarian transplantation in a monkey model did not improve graft survival, although their sample size was small (23).…”
Section: Discussionmentioning
confidence: 99%